The economic costs of COVID-19 in Sub-Saharan Africa: Insights from a simulation exercise for Ghana - Amewu, Sena; Asante, Seth; Pauw, Karl; Thurlow, James (European Association of Development Research and Training Institutes, 2020)
Globally, countries have resorted to social distancing, travel restrictions and economic lockdowns to reduce transmission of COVID-19. The socioeconomic costs of these blunt measures are expected to be high, especially in sub-Saharan Africa where many live hand-to-mouth and lack social safety nets. Social Accounting Matrix multiplier model results show that Ghana’s urban lockdown, although in force for only three weeks in April 2020, has likely caused GDP to fall by 27.9% during that period, while an additional 3.8 million Ghanaians temporarily became poor. Compared to the government’s revised GDP growth rate of 1.5% for 2020, the model predicts a contraction of 0.6 to 6.3% for 2020, depending on the speed of the recovery. The US$200 million budgeted for Ghana’s Coronavirus Alleviation Program will close only a small part of the estimated US$ 2.3 billion GDP gap between the fast recovery scenario and government’s revised GDP trajectory.